The outcome of the first 100 nasopharyngeal cancer patients in Thailand treated by helical tomotherapy - Chitapanarux I. (2017)
© 2017 Radiol Oncol. The aim of the study was to analyse of two-year loco-regional failure free survival (LRFFS), distant metastasis free survival (DMFS), overall survival (OS), and toxicity outcomes of the first 100 nasopharyngeal carcinoma patients in Thailand treated by helical tomotherapy. Between March 2012 and December 2015, 100 patients with non-metastatic nasopharyngeal carcinoma were treated by helical tomotherapy. All patients were treated by platinum-based concurrent chemoradiotherapy and adjuvant or neo-adjuvant chemotherapy. The median age was 51 years (interquartile ranges [IQR]: 42.5-57.0). The mean ± SD of D95% of planning target volume (PTV) 70, 59.4 and 54 were 70.2 ± 0.5, 59.8 ± 0.6, and 54.3 ± 0.8 Gy, respectively. The mean ± SD of conformity index, and homogeneity index were 0.89 ± 0.13 and 0.06 ± 0.07. Mean ± SD of D2 % of spinal cord and brainstem were 34.1 ± 4.4 and 53.3 ±6.3 Gy. Mean ± SD of D50 of contralateral and ipsilateral parotid gland were 28.4 ± 6.7 and 38.5 ± 11.2 Gy. At a median follow-up of 33 months (IQR: 25-41), the 2-year LRFFS, DMFS, OS were 94% (95%CI: 87-98%), 96% (95% CI: 89-98%), and 99% (95% CI: 93-100%), respectively. Acute grade 3 dermatitis, pharyngoesophagitis, and mucositis occurred in 5%, 51%, and 37%, respectively. Late pharyngoesophagitis grade 0 and 1 were found in 98% and 2% of patients. Late xerostomia grade 0, 1 and 2 were found in 17%, 78% and 5%, respectively. Helical tomotherapy offers good dosimetric performance and achieves excellent treatment outcome in nasopharyngeal carcinoma patients.